High HIV Prevalence Among Low Income and Laborers in the District of Purba Medinipur, West Bengal, India - Biswas, DK; Bhunia, R; Mishra, A (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Introduction: There were limited data of “People Living with HIV/AIDS” (PLHA). The data of PLHA were analyzed in time, place and person and socio-economic status and recommended for prevention of HIV infection. Objective of study were to describe the PLHAs in term of time, place and person distribution and their socio-demographic status, to detect the mode of transmission of HIV and to recommend for prevention of spread HIV infection and social security. Methodology: The information about socio-demographic status and exposure history of PLHAs since 2010 was collected. Data were analyzed by using Epi-info software. Results: Among 329 PLHAs, 165 (50%) were men and 42 (13%) were children <14 years and they acquired HIV through blood transfusion 26 (62%). A maximum 276 (84%) PLHAs were age group 15 - 45 years. Out of 25 Community Block in district, maximum PLHAs were distributed at Tamluk Block 56 (17%) followed by Paskura 43 (13%). Of PLHAs, 246 (75%) had family income rupees <2000.00 per month and 138 (38%) of them were laborer and 85 (26%) home maker (house-wife). Highest 289 (88%) of PLHAs acquired HIV through heterosexual route. Conclusion: Heterosexual transmission of HIV showed among low income and laborer. The counseling for safe sex practice, employment people and social amenities were recommended. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2012; IX(2) 1-4 DOI: http://dx.doi.org/10.3126/saarctb.v9i2.7970